(untitled) (Latakia University Journal -Biological Sciences Series, 2024)
The research was carried out in the Stemerkho facility for the production of agricultural mushrooms during 2022-2023 ,and included five treatments: control (without adding honey), adding honey at concentrations of 15, 20, 25, 30 ml/l to the malt agar (MEA) medium, with the aim of studying its effect on the growth of the mycelium of the mother culture, The research was carried out using a completely randomized design. The results of the average repetition of the experiment twice in a row in the years 2022-2023 showed that all honey addition treatments were superior to the control in terms of the start date of mycelium growth, the time required for its complete growth, growth speed, and growth coefficient. In terms of the diameter of the fungal colony, the treatment of adding honey with a concentration of 20 ml/l was superior to the honey treatment with a concentration of 15 ml/l, and the diameter reached (74.9, 68.7) mm and in turn, it was superior to the two honey treatments with a concentration of 25 ml/l and 30 ml/l, and the diameter reached (63.9, 64) mm, respectively. All of them exceeded the witness, which had a diameter of 52.2 mm.[1]